Entropy analysis of Darcy–Forchheimer flow of couple-stress TiO2-CoFe2O4/engine oil based hybrid nanofluid between two rotating disks considering hall effect - Sk Enamul; Seetalsmita Samal; Surender Ontela (Partial Differential Equations in Applied Mathematics)
This study investigates heat transfer and entropy production in Couple-Stress hybrid nanofluid flow between two spinning disks. It incorporates the Darcy–Forchheimer porous effects and the Hall effect. The hybrid nanofluid consists of titanium dioxide (TiO2) and cobalt ferrite (CoFe2O4) nanoparticles in the base fluid of engine oil. The governing equations are made dimensionless through similarity transformations. The semi-analytical methodology known as the homotopy analysis method (HAM) is then applied to the solution. Critical parameters such as the inertial coefficient, heat source parameter, nanoparticle concentration, and magnetic field parameter are analyzed graphically. These analyses explore their effects on velocity profiles, temperature distribution, and entropy generation. The findings demonstrate that radial velocity initially increases and then decreases with an increasing inertial coefficient, while axial velocity increases consistently. The temperature profile grows with a higher heat source parameter, reflecting enhanced internal heat generation. Entropy generation displays non-linear behavior concerning the heat source parameters. The Bejan number decreases near the disks due to efficient heat transfer. However, it increases in the central region, where thermal irreversibility dominates at higher values of volume fraction concentration of TiO2. These results provide valuable insights into the effects of nanoparticle concentration. They also shed light on the impact of thermal characteristics and flow parameters. This study optimizes thermal management and heat transfer systems in engineering applications. It offers guidance for improving energy efficiency in advanced fluid dynamics scenarios.